Mejora de la capacidad productiva y la gestión de inventarios para asegurar una reposición efectiva y constante durante el tiempo de producción en la empresa Induver - García Limones Ronnie Alexander, García Limones Ronnie Alexander (2022)
This research project is focused on the "Improvement of the productive capacity and inventory management to ensure an effective and constant replenishment during production time in the company Induver", in order to know the current situation of the company and propose possible solutions, through the use of methodologies such as 5'S (kaizen) and ABC inventory system, which are of support for the identification of organizational deficiencies that occur in the company Induver. Through the assistance of these methodologies, it was possible to observe the existence of problems in inventory management in addition to the lack of organization of the elements (equipment and/or tools) in specific areas. For this reason, it is necessary to make a proposal to improve the productive capacity and inventory management through the development and implementation of a range of formats (tables), which will support the effective use of methodologies allowing to identify the consumption of resources that prevent the development of production times. Keywords: capacity, methodology, organization, production.